2016
DOI: 10.1002/maco.201608881
|View full text |Cite
|
Sign up to set email alerts
|

Improving durability of reinforced concrete structures by recycling wet‐ground MSWI bottom ash

Abstract: Municipal solid waste incineration (MSWI) generates high amounts of bottom ash that, after grinding, could be used as mineral addition for concrete. Wet grinding of the bottom ash can prevent the risk of deleterious expansion due to hydrogen evolution, associated to the presence of metallic aluminium. The pozzolanic behavior of the bottom ash may improve concrete resistance to the penetration of aggressive species. Advantages of recycling wet-ground MSWI bottom ashes may even be higher when self-compacting con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 28 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…However, thermal treatments ( Figure 6(b)) were noted to improve the material reactivity, leading to both higher early strengths and long-term strengths that exceeded the control mix. Additional work by Carsana et al (2016) and Tang et al (2016), with treatments specifically aimed at reducing the metallic aluminium, showed that the associated expansive reaction can have a drastic impact on strength performance. Reductions in metallic aluminium contents and much improved mechanical performance were achieved using a combined metal separation plus wet grinding treatment (Carsana et al, 2016) and a combined thermal plus lower speed grinding treatment (Tang et al, 2016).…”
Section: Mortarmentioning
confidence: 99%
See 1 more Smart Citation
“…However, thermal treatments ( Figure 6(b)) were noted to improve the material reactivity, leading to both higher early strengths and long-term strengths that exceeded the control mix. Additional work by Carsana et al (2016) and Tang et al (2016), with treatments specifically aimed at reducing the metallic aluminium, showed that the associated expansive reaction can have a drastic impact on strength performance. Reductions in metallic aluminium contents and much improved mechanical performance were achieved using a combined metal separation plus wet grinding treatment (Carsana et al, 2016) and a combined thermal plus lower speed grinding treatment (Tang et al, 2016).…”
Section: Mortarmentioning
confidence: 99%
“…The wet grinding step is particularly effective because the aluminium fractions become more exposed as the particles fragment during grinding (Carsana et al, 2016) and, in the alkaline environment, the expansive reactions develop from the formation of aluminium hydroxide and hydrogen gas and are eventually depleted before the material is introduced into the cement mixture. A slower grinding speed can also be beneficial as it allows better removal of the dust-like particulates that reside on MIBA particle surfaces (which are believed to be the most reactive fractions) by means of inter-particle friction and, as a result, the subsequent expansive reactions in the cement environment are reduced (Tang et al, 2016).…”
Section: Mortarmentioning
confidence: 99%
“…& The publications that studied the behaviour of PLC in chloride-bearing exposure were divided into chloride ingress measurements and chloride-induced corrosion ( Figure 3). Some of the studies did not provide results for corresponding PC mixtures (Ahmad et al, 2014;Assie et al, 2006;Audenaert and De Schutter, 2009;Audenaert et al, 2007Audenaert et al, , 2010Beigi et al, 2013;Bertolini and Gastaldi, 2011;Bertolini et al, 2002Bertolini et al, , 2004aBolzoni et al, 2006Bolzoni et al, , 2014Brenna et al, 2013;Carsana et al, 2016;Chiker et al, 2016;Climent et al, 2006;Corinaldesi and Moriconi, 2004 1989 1990 1991 1992 1993 1994 1995 1996 1997 1998 1999 2000 2001 2002 2003 2004 2005 2006 2007 2008 2009 2016; Meira et al, 2014;Ramezanianpour and Afzali, 2015;Romano et al, 2013;Sánchez et al, 2008;Sfikas et al, 2013;Sistonen et al, 2008;Tittarelli and Moriconi, 2011;Yüksel et al, 2016;Zhang et al, 2016). Some publications contained duplicated data.…”
Section: Methodsmentioning
confidence: 99%
“…65 Moreover, being amorphous 66 and containing large quantities of silicon and calcium, glass is, in theory, pozzolanic if finely ground. [66][67][68][69][70][71] Many studies [72][73][74][75] have confirmed that ground-glass powder exhibits a good pozzolanic reactivity. 72,73 An increase of finely groundglass content, however, reduces the strength of concrete during the early stages due to a slower pozzolanic reaction compared to cement hydration and a lower cement content.…”
Section: Recycled Glassmentioning
confidence: 99%